Prawo kanoniczne – skostniałe, zmieniane czy odnawiane? - Jakubiak, Tomasz (Warszawskie Studia Teologiczne, 2017)
Following changes in law that have taken place even in the last years of the Church’s existence one certainly cannot say that it is fossilized. On one hand it listens to the needs, problems and life of the community of Faithful and on the other to the Revelation. It takes into account the achievements and development of theological, biblical, patristic and anthropological science. It is constantly changing.Are these changes well enough characterized by the term "renewal"?Given the nature of canon law as well as the objectives pursued by the Legislator in correcting/changing the law it seems that we can say that in most cases the Legislator changing the law also renewed it.The Church as the Legislator always has its eyes on Jesus and the Revelation that he gave to the Church. It is no wonder that all changes in the law are directly or indirectly guided by one main goal which is the salvation of man. This principle is superior in canon law to this day. Revelation is the foundation of the law and a framework of all the changes taking place in it.As the community of the Church is subjected to historical determinants therefore the law governing community life of the Church is also a subject of historical determinants.Readiness to take into account progress and changes in theological, anthropological, biblical, patristic and legal sciences shows that the Legislator is not only changing the law but also renews it.